Miskonsepsi Pembelajaran IPAS Siswa Kelas IV Sekolah Dasar - Rahmawati, Putri; Kurniawati, Wahyu (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2024)
The purpose of the study was to clarify or explain the misconceptions in IPAS learning for force material for grade IV elementary school students. Data collection methods using tests in the form of diagnostic tests and interviews. The sampling method is a saturated sample of all fourth grade elementary school students. The research data were analyzed using quantitative descriptive analysis. Based on the research results, an average of 39.75% of misconceptions experienced by elementary school students or 15 out of 39 students are included in the "moderate" misconception category. The highest misconceptions in the sub-indicators were about "The Effect of Force on Objects" with a percentage of 51%, the sub-indicator "Megnet, a magical object" with a misconception percentage of 26%, the sub-indicator "Elastic Objects" with a misconception percentage of 49%, and the sub-indicator "Why We Don't Float in the Air" with a misconception percentage of 33%. The factors that cause students' misconceptions or misunderstandings are the students themselves, the situation and the teaching method.